Serum Concentration of Molybdenum in Chronic Renal Failure Patients Requiring Hemodialysis - Manuti, Jawad K.; Al-Rubaye, Faisal Gh.; Khudhair, Mahmood S. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: High serum molybdenum level may contribute to dialysis related bone disease in patients requiring long term hemodialysis in fact massive molybdenum accumulation causes joint deformity and arthritisObjective: To asses the level of molybdenum in uremic patients requiring long term hemodialysis and impact of hemodialysis on the serum level of molybdenum before and after hemodialysisPatients and methods: Eighty patients complain from chronic renal failure on long term hemodialysis aged (16 to 65) years, serum molybdenum was measured before and after hemodialysisResult: The mean serum molybdenum level in 80 patients requiring long term hemodialysis was elevated before dialysis (0.29 + 0.17 nmol/mL) and even after dialysis (0.16 + 0.05 nmol/mL) in comparison to the normal value (normal 0.02------0.13 nmol/ml).The value significantly decrease from 0.29 + 0.17 nmol/mL before hemodialysis to 0.16 + 0.05 nmol/mL after hemodialysis (P.value